2023
DOI: 10.1021/acs.est.2c09553
|View full text |Cite
|
Sign up to set email alerts
|

Risk Control Values and Remediation Goals for Benzo[a]pyrene in Contaminated Sites: Sectoral Characteristics, Temporal Trends, and Empirical Implications

Abstract: Benzo[a]pyrene (BaP) is a highly carcinogenic pollutant of global concern. There is a need for a comprehensive assessment of regulation decisions for BaP-contaminated site management. Herein, we present a quantitative evaluation of remediation decisions from 206 contaminated sites throughout China between 2011 and 2021 using the cumulative distribution function (CDF) and related statistical methodologies. Generally, remediation decisions seek to establish remediation goals (RGs) based on the risk control value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In response, governments and environmental regulators worldwide are dedicated to adopting green, low-carbon strategies for sustainable land remediation [4,5]. A broad spectrum of soil remediation technologies exists, exemplified by the United States Superfund's application of nearly 30 technologies across 1468 contaminated sites.…”
Section: Introductionmentioning
confidence: 99%
“…In response, governments and environmental regulators worldwide are dedicated to adopting green, low-carbon strategies for sustainable land remediation [4,5]. A broad spectrum of soil remediation technologies exists, exemplified by the United States Superfund's application of nearly 30 technologies across 1468 contaminated sites.…”
Section: Introductionmentioning
confidence: 99%
“…We used a multi-omics approach, including metagenomics, viromics, metatranscriptomics, and bioinformatics, to investigate the earthworm intestinal virome and its interaction with bacteriome under environmental pollution stress. Benzo[a]pyrene (BaP), a carcinogenic polycyclic aromatic hydrocarbon (PAH) was selected as a test soil pollutant because of its widespread presence and recalcitrance in soils [ 17 ] as well as its tendency to accumulate in earthworm gut [ 18 , 19 ]. Multiple phage identification assays were adopted to characterize the earthworm intestinal phage community profile and its response to BaP-induced stress.…”
Section: Introductionmentioning
confidence: 99%
“…Jennings et al [10] found that the RGVs for seven carcinogenic or mutagenic PAHs varied over 6.3-7.2 orders of magnitude worldwide under different land uses. The soil regulatory guidance values (RGVs) for benzo(a)pyrene under sensitive land use in different counties ranged from 0.11 to 1 mg/kg due to differences in regulations, theoretical basis, and soil properties [11]. Human exposure to PAHs is mainly through three pathways including oral ingestion, skin contact, and inhalation, with the oral ingestion pathway being the most important [12,13].…”
Section: Introductionmentioning
confidence: 99%